New Frontiers in Anxiety Research: The Translational Potential of the Bed Nucleus of the Stria Terminalis - Knight, Lindsay K.; Depue, Brendan E. (Frontiers in Psychiatry, 2019)
After decades of being overshadowed by the amygdala, new perspectives suggest a tiny basal forebrain region known as the bed nucleus of the stria terminalis (BNST) may hold key insights into understanding and treating anxiety disorders. Converging research indicates that the amygdala and BNST play complementary but distinct functional roles during threat processing, with the BNST specializing in the detection of a potential threat to maintain hypervigilance and anxiety, while the amygdala responds to the perceived presence of an aversive stimulus (i.e. fear). Therefore, given that human anxiety is largely driven by future-oriented hypothetical threats that may never occur, studies involving the BNST stand at the forefront of essential future research with the potential to bring about profound insights for understanding and treating anxiety disorders. In this article, we present a narrative review on the BNST, summarizing its roles in anxiety and the stress response, and highlighting the most recent advances in the clinical realm. Furthermore, we discuss oversights in the current state of anxiety research and identify avenues for future exploration.